Acute outcomes of acupuncture and dry needling over peripheral acute fatigue in untrained healthy volunteers: A randomized controlled clinical trial - Antonino, Gabriel; Ferreira, Ana Paula; Mendonça, Horianna; Shirahige, Lívia; Montenegro, Eduardo; Guerino, Marcelo; Filho, Alberto; Bernardo-Filho, Mario; Campos, Shirley Lima; Leite, Wagner Souza; Monte-Silva, Kátia; Taiar, Redha; et al. (Heliyon, 2023)
Peripheral acute fatigue (PAF) is defined as when the skeletal muscle is incapable of generating power. We aimed to investigate the acute effects of traditional Chinese acupuncture (TCA) and dry needling (DN) over PAF induced on the biceps brachii of untrained healthy volunteers. We conducted a randomized, single-blind controlled clinical trial. All volunteers (n = 45) underwent fatigue induction protocols repeated before and after treatment with TCA (TCA group; TCAg; n = 15), DN (DN group; DNg; n = 15), and rest (control group; Cg; n = 15). Assessments of PAF, skin temperature, and exercise time occur before and after each event: 1st fatigue induction (FI), treatment, and 2nd FI. We used repeated measures ANOVA adjusted with Bonferroni post hoc test to determine any change in tested variables (PAF-VAS, PAF-EMG, and skin temperature) at different time points compared to the baseline. Paired Samples t-test was used for the variable exercise times. All statistical tests considered’ the significance level at p ≤ 0,05. There was no difference between groups in acute fatigue recovery (p = 0.19). All intragroup analyses were significant (p ≤ 0.05) and all volunteers show a reduction in fatigue perception after treatment (p ≤ 0,05), however, exercise time did not ameliorate after TCA or DN (p > 0.77). A single session of TCA and, DN can equally reduce fatigue, temperature, and exercise time over PAF induced on biceps brachii of untrained healthy volunteers.
Keywords: Acupuncture; Dry needling; Muscle fatigue